The concatenation of association between gastroesophageal reflux and obstructive adenotonsillar hypertrophy. (December 2020) - Sagar, Milind; Sagar, Prem; Kabra, S.K.; Kumar, Rajeev; Mallick, Saumyaranjan
Abstract: Objectives: Gastroesophageal reflux (GER) is frequently seen in patients with adenotonsillar hypertrophy. However, the sequential association between GER and adenotonsillar hypertrophy is unknown. This leads to unpredictable outcomes while treating patients of adenotonsillar hypertrophy with GER. The objective of this study is to evaluate the prevalence of GER and gastroesophageal reflux disease (GERD) in paediatric patients with obstructive adenotonsillar hypertrophy (OATH), and to assess the effect of adenotonsillectomy (AT) on GER as well as GERD. Methods: In this prospective cohort study, consecutive pediatric patients with grade III/IV hypertrophy of adenoid or/and tonsillar tissue who were planned for AT were recruited after excluding comorbidities predisposing to GER. Symptoms of GERD using Gastro Esophageal Reflux Questionnaire for Young Children (GERQ-YC) and Reflux Indices (RI) obtained from 24-h ambulatory esophageal pH monitoring were evaluated in all patients pre-operatively and 12 weeks following AT. Results: A total of 49 patients with OATH with average age of 6 years were included in this study. With a RI of >4.3% as the threshold for making the diagnosis of GER on esophageal pH monitoring, the prevalence of GER was 20.4%. The average RI preoperatively was 15.7% which reduced to 1.7% following AT (p = 0.004). Among the 10 patients with preoperative GER, 80% of the patients had no evidence of GER after surgery. New incidences of GER was not observed post operatively in this cohort. As per the GER symptom scoring system, 31% of the parents reported GERD pre-operatively which resolved completely in all patients following surgery. Conclusions: – In this study, the prevalence of GER proven by 24 h ambulatory esophageal pH monitoring is 20% in pediatric patients with OATH. Following AT, GER resolved in 80% of cases and was reduced substantially in the remaining cases in the subset of patients with pre-operative GER. The symptoms of GERD based on parents' recall of child's previous symptoms may not accurately represent presence of GER. Our results suggest that OATH can result in GER due to increased negative intra-thoracic pressure as a result of breathing against an obstructed upper airway and hence, GER subsides following surgical removal of the obstructive pathology. To establish this concatenational association of OATH and GER, larger studies are mandated.